2022
DOI: 10.1111/1471-0528.17347
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcomes following a diagnosis of Hodgkin lymphoma during or prior to pregnancy: A systematic review

Abstract: Background The initial peak incidence of Hodgkin lymphoma (HL) occurs during reproductive years. Objectives Synthesise published literature on the relationship between HL and maternal and perinatal outcomes. Search strategy Systematic search of PubMed/Medline, Cochrane Library, Scopus, Embase and Science Direct from inception to June 2022, supplemented by hand‐searching reference lists. Selection criteria Two reviewers independently reviewed titles, abstracts and full‐text articles. Published studies containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…These findings correspond to the literature data, which have shown that, in general, the diagnosis of most cancer types during pregnancy or lactation (except melanoma, breast and ovarian cancers) does not increase the risk of cause‐specific death 28 . Moreover, as with most common malignancies diagnosed during pregnancy, studies indicate that the rates of adverse pregnancy outcomes are similar in women with a Hodgkin lymphoma and those in the general pregnant population 29,30 . In addition, no significant increase in maternal morbidity or mortality was registered if ovarian malignancies complicated pregnancy 31 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings correspond to the literature data, which have shown that, in general, the diagnosis of most cancer types during pregnancy or lactation (except melanoma, breast and ovarian cancers) does not increase the risk of cause‐specific death 28 . Moreover, as with most common malignancies diagnosed during pregnancy, studies indicate that the rates of adverse pregnancy outcomes are similar in women with a Hodgkin lymphoma and those in the general pregnant population 29,30 . In addition, no significant increase in maternal morbidity or mortality was registered if ovarian malignancies complicated pregnancy 31 …”
Section: Discussionsupporting
confidence: 87%
“…28 Moreover, as with most common malignancies diagnosed during pregnancy, studies indicate that the rates of adverse pregnancy outcomes are similar in women with a Hodgkin lymphoma and those in the general pregnant population. 29,30 In addition, no significant increase in maternal morbidity or mortality was registered if ovarian malignancies complicated pregnancy. 31 Studies conducted in the previous decade have reported an increased risk for induced abortion, stillbirth, preterm birth, growth restrictions, neonatal intensive care unit admission, and neonatal death in pregnancies complicated by cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Dear Dr. Papageorghiou, We would like to take this opportunity to respond to the letter authored by Shen et al 1 in relation to our recently published paper. 2 We thank the authors for their interest in our paper and their comments regarding the use of the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system.…”
Section: Au T Hor C On T R I Bu T Ion Smentioning
confidence: 99%
“…Dear Dr. Papageorghiou, We read with great interest the systematic review by Houlihan et al 1 examining whether a previous or current diagnosis of Hodgkin lymphoma (HL) is associated with adverse maternal and perinatal outcomes. They included 33 observational studies (18 case series and 15 cohort studies) and concluded that there were no increased rates of most adverse pregnancy outcomes among women with a current or previous diagnosis of HL compared with the general pregnant population, and that the studies had a low to very low quality of evidence using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system.…”
mentioning
confidence: 99%
“…Dear Dr. Papageorghiou, We would like to take this opportunity to respond to the letter authored by Shen et al 1 in relation to our recently published paper. 2 We thank the authors for their interest in our paper and their comments regarding the use of the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system.…”
Section: Authors' Replymentioning
confidence: 99%